Emotional responses to bullying among Japanese adolescents: Gender, context, and incidence visibility. Issue 2 (3rd April 2018) - Aoyama, Ikuko; Yanagida, Takuya; Wright, Michelle F.
ABSTRACT: Bullying can occur with differing levels of visibility (e.g., public or private) and in various contexts (e.g., face-to-face or online). This study examined 474 Japanese middle-school students' emotional responses to public versus private bullying scenarios in face-to-face and digital contexts. After reading four hypothetical bullying vignettes, participants described how they would have felt in each. Students felt sadder and more embarrassed for public bullying scenarios. No differences in anger were observed regarding visibility, but students reported feeling angrier in cyberbullying than face-to-face scenarios. As for gender differences, girls were more likely to feel sad and embarrassed than boys; however, no differences were seen in emotional responses based on visibility or context. The results suggest it is important to consider the context and incident visibility as well as different types of bullying when developing educational programs for bullying prevention.